Lifetime number of years of menstruation as a risk index for postmenopausal endometrial cancer in the Norwegian Women and Cancer Study - Gavrilyuk, Oxana; Braaten, Tonje; Weiderpass, Elisabete; Licaj, Idlir; Lund, Eiliv (Wiley Blackwell, 2018)
IntroductionLifetime number of years of menstruation (LNYM) reflects a woman's cumulative exposure to endogenous estrogen and can be used as a measure of the combined effect of reproductive factors related to endometrial cancer (EC) risk. Material and methodsWe aimed to study the association between LNYM and EC risk among postmenopausal women and calculate the population attributable fraction of EC for different LNYM categories. Our study sample consisted of 117589 women from the Norwegian Women and Cancer (NOWAC) Study. All women were aged 30-70years at enrollment and completed a baseline questionnaire between 1991 and 2006. Women were followed up for EC to December 2014 through linkages to national registries. We used Cox proportional hazards models to estimate hazard ratios with 95% confidence intervals (95% CIs), adjusted for potential confounders. ResultsIn all, 720 women developed EC. We found a statistically significant, positive dose-response relationship between LNYM and EC, with a 9.1% higher risk for each additional year of LNYM (P for trend ConclusionsOur study supports that increasing LNYM is an important and independent predictor of EC risk. Peer reviewed